2000
DOI: 10.1590/s1516-35982000000500014
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de esquemas de seleção alternativos para bovinos Zebus de dupla aptidão

Abstract: RESUMO -Utilizando-se simulação determinística, foram avaliados seis esquemas de melhoramento, com diferentes grupos de informações: (1) somente características de crescimento, (2) somente características leiteiras, (3) características de crescimento e reprodutivas, (4) características leiteiras e reprodutivas, (5) características de crescimento e leiteiras e (6) características de crescimento, leiteiras e reprodutivas. Avaliaram-se também a resposta à variação no uso de touros provados por meio do teste de pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…However, prioritization at secondary level, obtained when the quantitative questionnaire was applied to customers, indicated that the concern with product-related items is still predominant, with emphasis on genetic and performance traits. This may be related to the large impact of sire choice in herd genetic quality (Lôbo, 2000;Giacomini, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…However, prioritization at secondary level, obtained when the quantitative questionnaire was applied to customers, indicated that the concern with product-related items is still predominant, with emphasis on genetic and performance traits. This may be related to the large impact of sire choice in herd genetic quality (Lôbo, 2000;Giacomini, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the results depend on the environmental, genetic and value relationships between the traits involved. These relationships, if neglected, may result in losses in productivity and response to selection in each trait, and in the remuneration of these by industry (Lôbo, Madalena, & Penna, 2000;Madalena, 2000) The Gyr breed was a pioneer among the zebu breeds in implanting a genetic breeding program for milk, beginning precisely in 1985. The Guzerá breed, in turn, had the genetic breeding program installed 09 years after the Gyr breed.…”
Section: Introductionmentioning
confidence: 99%